Effects of video‐based flipped class instruction on subject reading motivation - Tse, Wai S.; Choi, Lai Y. A.; Tang, Wing S. (British journal of educational technology, 2019)
Video‐based flipped class instruction can strengthen the learning motivation of students. The effectiveness of flipped class instruction on teaching effectiveness and subject satisfaction has been evaluated previously. The present study aims to examine the impact of two aspects of subject reading motivation. A total of 100 secondary school students were recruited from 4 classes of 25 students (ie, video‐based flipped Mathematics class, traditional Mathematics class, video‐based flipped Liberal Studies (LS) class and traditional LS class) in two local secondary schools. The same teachers taught both the traditional and video‐based flipped classes in their subject. The students filled in questionnaires which measured: motivation for general reading; motivation for subject reading; academic subject satisfaction and perceived teaching effectiveness of the teachers. Analysis of covariance controlling for motivation for general reading revealed that students in the flipped classes reported significantly lower motivation for subject reading including reading curiosity, reading importance and reading compliance (t (1,98) = 10.52, p < 0.001; t (1,98) = 7.68, p < 0.001; t (1,98) = 20.39, p < 0.001, respectively). However, students in the flipped classes reported significantly higher satisfaction and teaching effectiveness than those in the traditional classes (t (1,98) = −15.61. p < 0.001; t (1,98) = −11.98, p <0.001, respectively). A partial correlation controlling for motivation for general reading indicated that motivation for subject reading was negatively associated with academic subject satisfaction and perceived teaching effectiveness of teachers (rs ranged from −0.51 to −0.62, p < 0.001). Video‐based flipped class instruction was not only related to increased academic subject satisfaction and teaching effectiveness but also associated with lower motivation for subject reading. These findings suggest that video‐based flipped class instruction had limited capability to strengthen the learning motivation of students.